ANALYSING THE DRIVING FORCE OF ENTREPRENURSHIP INTENTION AMONG STUDENTS (CASE STUDY: THE INTENTION OF IBA STUDENTS AT SAM RATULANGI UNIVERSITY TO RUN A BUSINESS) - Garera, Debora P.; Massie, James D. D.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Driving forces mean the forces that can give the stimulus to the subject; in this case the stimulus for the student’s entrepreneurial intention. Without the right driving forces; student’s entrepreneurial intention cannot be achieved in the end and thus students in the future may not consider entrepreneur as one of the alternatives for their careers. The research aims to gain more comprehensive understanding regarding the driving force of entrepreneurship intention among students in IBA. This study uses a qualitative method and using interview as the tool to collect data from informants. The findings of this study show that all of the driving forces which are flexibility, family influence and responsibility, teamwork, financial needs and control act as an important driving force that can affect the entrepreneurial intention of college students. Meaning that by emphasizing these driving forces; it can create a better chance for college students to choose entrepreneurship as a major career choice in the future. Based on the result, the major recommendation is regarding the emphasis of these driving forces within college or other educational institution in order to increase the chance of people choosing entrepreneurs as their career path in the future.   Keywords: entrepreneurial intention, financial needs, family influence, flexibility, teamwork, control